Additive manufacturing of microchannel scaffolds with improved biocompatibility and nutrient diffusion for tissue engineering - Putri, Nur Rofiqoh Eviana (2024)
Scaffold architecture and properties to mimic the native tissue are the key challenges for successful tissue engineering. Improving scaffold architecture by incorporation of microchannels could enhance its nutrient and oxygen diffusion and provide an effective viable cell distribution, which leads to better tissue regeneration. Without vascularisation, the transport of nutrients and oxygen to the cells cannot be optimum, leading to cell death. Several techniques have been developed to fabricate microchannel scaffolds, but they are not able to mimic the complex architecture of the native tissue due to the inflexibility of controlling the structure. To solve those problems, additive manufacturing called three-dimensional (3D) printing offers the ability to fabricate complex microchannel scaffolds and mimic the native tissue in a single printing process. Either directly or indirectly using sacrificial ink, 3D printing has been widely developed and can be used for microchannel scaffold fabrication.